2017
DOI: 10.18502/kls.v3i4.699
|View full text |Cite
|
Sign up to set email alerts
|

Potency of Endo-Exopolysaccharide from Porphyridium cruentum (S.F.Gray) Nägeli as Antioxidant (DPPH) and Biological Toxicity (BSLT)

Abstract: Sources of antioxidants are abundant in nature, one of which is derived from microalgae. Microalgae species that have potentially to be developed as a producer of antioxidant compounds is Porphyridium cruentum (S. F. Gray) Nägeli. P. cruentum is a red microalga (Rhodophyceae) and has been known as polysaccharides producer (exopolysaccharide and endopolysaccharide) and as an antioxidant. This study aims to determine antioxidant activity of the extracts and biological toxicity of endo-and exopolysaccharide P. cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Similarly, the monosaccharide composition of PTP mainly included xylose, fucose, glucose and galactose. Fucose was not reported by Agustini & Kusmiati (2017), which may be due to the different origins of the algae. In this paper, we determined not only the monosaccharide composition but also the total sugar, sulfate contents and Mw (29.94%, 20.36%, and 4,810 kDa, respectively) and found that PTP is a complicated sulfated polysaccharide.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Similarly, the monosaccharide composition of PTP mainly included xylose, fucose, glucose and galactose. Fucose was not reported by Agustini & Kusmiati (2017), which may be due to the different origins of the algae. In this paper, we determined not only the monosaccharide composition but also the total sugar, sulfate contents and Mw (29.94%, 20.36%, and 4,810 kDa, respectively) and found that PTP is a complicated sulfated polysaccharide.…”
Section: Discussionmentioning
confidence: 92%
“…exhibited significant cytotoxicity against a variety of cancer cells, which meant that the polysaccharides might be a potential anticancer chemotherapeutic agent. For PTP, some references reported antioxidant (Agustini & Kusmiati, 2017), anti-obesity (Kim et al, 2016), anti-inflammatory, and immunomodulatory activities (Kim et al, 2013; Guzmán et al, 2003). A novel fatty alcohol ester isolated from PTP showed apoptotic anticancer activity (Samarakoon et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…exhibited significant cytotoxicity against a variety of cancer cells, which meant that the polysaccharides might be a potential anticancer chemotherapeutic agent. For Phaeodactylum tricornutum, some references reported antioxidant (Agustini et al, 2017), anti-obesity (Kim et al, 2016), anti-inflammatory and immunomodulatory activities (Kim et al, 2013;Guzmán et al, 2003). A novel fatty alcohol ester isolated from Phaeodactylum tricornutum showed apoptotic anticancer activity (Samarakoon et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A novel fatty alcohol ester isolated from Phaeodactylum tricornutum showed apoptotic anticancer activity (Samarakoon et al, 2014). Agustini et al(2017), which may be due to the different origins of the algae. In this paper, we determined not only the monosaccharide composition but also the total sugar, sulfate contents and Mw (29.94%, 20.36% and 4810 kDa, respectively) and found that PTP is a complicated sulfated polysaccharide.…”
Section: Discussionmentioning
confidence: 99%